ANALISIS SIFAT FISIK DAN MEKANIK GEOPOLYMER FOAM CONCRETE DENGAN VARIASI RASIO FOAMING AGENT DAN AIR (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2022)
Geopolymer is the synthesis of inorganic natural materials through a polymerization process. The mainingredients in the manufacture of geopolymers are materials containing silica and alumina. Geopolymermaterial can be obtained from coal industry waste products such as fly ash. Innovative technology inmanufacturing foam concrete is widely used in building construction, such as using earthquake-resistantbuilding walls and energy-efficient buildings. In this study, geopolymer foam concrete was manufacturedby combining a mixture of geopolymer and a mixture of foam. A solution of 14 M NaOH and Na2SiO3with a ratio of 2.5 was used as an activator. Fly ash is a precursor, and the ratio of foaming agent andwater is 1:20, 1:30, and 1:40, which is used as a material for making foam. This study aimed todetermine geopolymer foam concrete's physical and mechanical properties with various foaming agentsand water. The results of testing for air content in fresh concrete indicate that the use of more foamingagents in the manufacture of foam can improve the quality of the foam and reduce the air content of theconcrete so that it can increase the compressive strength of the test object. The use of fewer foamingagents can reduce the density of geopolymer foam concrete.